The role of the autonomic nervous system in control of cardiac and air-breathing responses to sustained aerobic exercise in the African sharptooth catfish Clarias gariepinus - Blasco, Felipe R. [UNESP]; McKenzie, David J.; Taylor, Edwin W.; Rantin, F. Tadeu (Elsevier B.V., 2017)
Clarias gariepinus is a facultative air-breathing catfish that exhibits changes in heart rate (f(H)) associated with air breaths (AB). A transient bradycardia prior to the AB is followed by sustained tachycardia during breath-hold. This study evaluated air-breathing and cardiac responses to sustained aerobic exercise in juveniles (total length similar to 20 cm), and how exercise influenced variations in f(H) associated with AB. In particular, it investigated the role of adrenergic and cholinergic control in cardiac responses, and effects of pharmacological abolition of this control on air-breathing responses. Sustained exercise at 15, 30 and 45 cm s(-1) in a swim tunnel caused significant increases in f(AB) and f(H), from approximately 5 breaths h(-1) and 60 heartbeats min(-1) at the lowest speed, to over 60 breaths h(-1) and 100 beats min(-1) at the highest, respectively. There was a progressive decline in the degree of variation in f(H), around each AB, as f(AB) increased with exercise intensity. Total autonomic blockade abolished all variation in fH during exercise, and around each AB, but f(AB) responses were the same as in untreated animals. Cardiac responses were exclusively due to modulation of inhibitory cholinergic tone, which varied from >100% at the lowest speed to <10% at the highest. Cholinergic blockade had no effect on f(AB) compared to untreated fish. Excitatory beta-adrenergic tone was approximately 20% and did not vary with swimming speed, but its blockade increased f(AB) at all speeds, compared to untreated animals. This reveals complex effects of autonomic control on air-breathing during exercise in C. gariepinus, which deserve further investigation. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Adrenergic tone; Cholinergic tone; Heart rate; Swimming